Sulfur Constraints on the Carbon Cycle of a Blanket Bog Peatland. Issue 8 (21st August 2021) - Boothroyd, I. M.; Worrall, F.; Moody, C. S.; Clay, G. D.; Abbott, G. D.; Rose, R.
Abstract: The reduction of sulfate (SO4 2− ) represents an alternative terminal electron acceptor for the oxidation of organic matter in peat soils. The greenhouse gas budget in peatlands will be constrained by how much a peatland can utilize SO4 2− reduction as an alternative to methanogenesis. Using records of atmospheric deposition and stream chemistry coupled with elemental analysis of peat soil, vegetation, particulate organic matter (POM) and dissolved organic matter (DOM), this study estimated a 23‐years long sulfur (S) budget for a blanket bog‐covered catchment in the North Pennines, England. The study showed that: (a) Atmospheric deposition of total S significantly declined over the study period from 2.4 to 0.5 t S/km 2 /yr. (b) Long term accumulation of S into deep peat at 1 m depth averaged 127 kg S/km 2 /yr. (c) Total S fluvial flux peaked as 4.5 t S/km 2 /yr with an average of 0.7 t S/km 2 /yr. (d) On average, over 23 years, 0.25 t S/km 2 /yr were reduced to either mineral sulphides or hydrogen sulphide; however, in eight out of the 23 years the catchment was a net producer of S to the streams of the catchment. At maximum observed, S reduction capacity the peatland was capable of a net removal of 71% of atmospheric S deposition. Allowing for the efficiency of energy transfer in the redox process and the oxidation state of peat organic matter means that for every mole of SO4 2− reduced, 1.69 moles of CO2 were produced, and an average of 0.47 t C/km 2 /yr are diverted from methanogenesis. Plain Language Summary: Peatlands are important terrestrial carbon (C) stores, with more carbon stored in peatlands than in the atmosphere. The very existence of peatlands relies on the fate or organic matter and the carbon budget is, therefore, a statement of ecosystem's future. The C budget of the peatland can be viewed as a series of reduction‐oxidation reactions. Carbon dioxide (CO2 ) from the atmosphere is fixed in to plant organic matter by photosynthesis. As organic matter transfers into the peat profile, the organic matter is transformed to CO2, methane (CH4 ), dissolved organic matter (DOM) and lost as particulate organic matter (POM). All but the transformation to POM requires a terminal electron acceptor, the most efficient of which is oxygen, followed by nitrate, but both of these are rapidly consumed in the water‐logged conditions of peatlands which could lead to production of the powerful greenhouse gas—methane. The alternative electron acceptors that could limit organic matter loss are iron and sulfate. In this study, we use detailed long term records, coupled with elemental composition measurements, from an peatland in the UK to show that for every tonne of S removed by the peatland 0.23 tonnes of carbon are diverted from methane loss. Key Points: Study evaluates the Sulfur (S) budget of a peatland to assess controls on C and greenhouse gas budgets The peat was accumulating 127 kg S/km 2 /yr, and reducing 0.25 t S/km 2 /yr, but in 8 out of 23 years the catchment was a net producer of S The peatland was capable of removing 71% of atmospheric deposition and diverting 0.47 t C/km 2 /yr are diverted from methanogenesis